No rastro das terras devolutas no litoral sul da Paraíba : um estudo da grilagem na formação da propriedade privada da terra - Spinelli, Lucas Gebara (2022)
This thesis intends to analyze the formation of private land ownership on the South coast of Paraiba from the theoretical-methodological perspective of the preavious accumulation of capital in the territorial formation of the South Coast of Paraiba, starting with the study of the chain of ownership of Fazenda Garapú, occupied by the MST (Landless Workers Movement) in 2017 and where two landless workers were assassinated in 2018. For this purpose, this study will present, from chapter 2 and on, an overview of the consolidation of private land ownership in Brazil and the land market that, since the colonial period, is based on legal forms of land dominiality guided by the private logic of land appropriation. Such formal pre-private propriety legal forms became predominant in opposition to peasant, indigenous and quilombola lands, conquered and occupied by the growing poor and free rural population in the country. Especially in Paraíba, at the end of the 18th century and throughout the 19th century, we observed the wide territorialization of the population over areas not being used by the large sugarcane monoculture. The Brazilian Constitution of 1824 considered private property as sacred, which kick-started the consolidation of large land areas in the name of rural oligarchies from the sesmarias and land tenures, both instituted since colonial times. The colonial legacy in the territorial planning of the country would give way to a territorial formation characterized by the increasing concentration of land in the hands of large squatter farmers, to the detriment of small land owners. The Land Law of 1850 would aggravate the scenario, creating the concept of vacant lands as synonymous with “land without legal owner”. Said law converted most of the country's land into a vast state land stock available to powerful land owner, to the detriment of their occupants of tribal and village indigenous origin, quilombola and small farmers. From these two legal frameworks (from 1824 to 1850) we observed a list of land-grabbing actions, systematically created by agents of the land market to enable the forgery of documentation “proving” dominial ancestry, briefly understood as the invention of time marks associating particulars to a given rural extension. Although always updated in the face of the country's land-use legislation, this list of land-grabbing practices made it possible to concentrate land on an increasing scale by the country's nascent industrial capitalism at the end of the 19th century and the beginning of the 20th century, who simultaneously explored wage labor and land income (coming from the sale or rent of the area). Throughout the 20th century, these procedures continue to be used, circumventing legislation and agrarian law. Especially in Paraíba, we highlight the case of the south coast as an example of a territorial formation characterized by the concentration of private land ownership. In chapters 3 and 4 we demonstrate how the different moments of territorial planning were manipulated in favor of rural oligarchies eager for the expansion of their land domains over common lands (peasants, indigenous peoples, quilombolas). By researching source material of that time and undertaking field studies, mapping and production of cartography and chronology of facts linked to the formation of large rural properties of the south coast, we observed the reproduction of the list of land-grabbing practices, which are based in part on the legally inaccessible heritage of the Lundgren family. These acted as pivots for a secular squatting of public lands on the southern coast, which ensured the accumulation of private property and the appropriation of land rent by five large groups of private landowners. Private lands originated and consolidated in land grabbing.